Electronic Student Worksheets to Train Scientific Literacy in Chemical Equilibrium Material - Machfiro, Fitani Wardha; Lutfi, Achmad (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2023)
The research aims to determine the level of effectiveness of using electronic student worksheets to train students' scientific literacy skills on chemical equilibrium material. The research design used the one-group pretest-posttest method. The sample in this study was class XI IPA, which consisted of 35 students. The research instrument was a pretest-posttest test instrument. The data obtained were analyzed by the N-gain test with the condition that the N-gain reached 76% and the classical condition with the condition ≥85% The results of the analysis show that the N-gain is 76.50%, and the classical completeness test is 97.14%. From the analysis, it can be concluded that electronic student worksheets are effective for training scientific literacy skills in chemical equilibrium material.